P04.02 A novel cancer immunotherapy combines rMVA-CD40L with tumor targeting antibodies. (1st October 2020) - Hinterberger, M; Medina-Echeverz, J; Testori, M; Geiger, M; Giessel, R; Bathke, B; Kassub, R; Gräbnitz, F; Fiore, G; Wennier, S; Chaplin, P; Suter, M; et al.
Abstract : Background: Virus-based vaccines and appropriate costimulation potently enhance antigen-specific T cell immunity against cancer. In the present study, we exploit both innate and adaptive immune responses triggered by a novel recombinant modified vaccinia virus Ankara (rMVA) encoding a Tumor-Associated Antigen (TAA) and the costimulatory CD40L against solid tumors in combination regimes to overcome tumor-induced resistance to immunotherapy. Material and Methods: Subcutaneous murine tumors were induced in C57BL/6 or Balb/c mice using syngeneic tumor cell lines. When tumors were established (60–80 mm 3 ) mice were intravenously injected with rMVA-CD40L. Tumor growth monitoring and immune cell analysis was performed. Results: Therapeutic treatment with rMVA-CD40L resulted in the control of established tumors in several independent tumor models. This antitumor effect was based on the generation of non-exhausted, systemic tumor-specific cytotoxic CD8 + T cells that was essential for therapeutic efficacy. Strikingly, rMVA-CD40L also induced strong NK cell activation and enhanced cytotoxicity. Moreover, the combination of rMVA-CD40L and tumor targeting antibodies resulted in increased therapeutic antitumor efficacy. This therapeutic combination relied on Fcγ receptor-expressing immune cells as well as on NK cells. Conclusion: We describe a novel and translationally relevant therapeutic synergy between viral vaccination and CD40L costimulation. We show strengthened antitumor immune responses when both rMVA-CD40L-induced innate and adaptive immune mechanisms are exploited by combining immunotherapeutic regimes, such as TAA targeting antibodies. This finding could have a direct positive impact in therapeutic regimens where TAA targeting antibodies could be employed. Disclosure Information: M. Hinterberger: A. Employment (full or part-time); Significant; Bavarian Nordic. J. Medina-Echeverz: A. Employment (full or part-time); Significant; Bavarian Nordic. M. Testori: A. Employment (full or part-time); Significant; Bavarian Nordic. M. Geiger: A. Employment (full or part-time); Significant; Bavarian Nordic. R. Giessel: A. Employment (full or part-time); Significant; Bavarian Nordic. B. Bathke: A. Employment (full or part-time); Significant; Bavarian Nordic. R. Kassub: A. Employment (full or part-time); Significant; Bavarian Nordic. F. Gräbnitz: A. Employment (full or part-time); Significant; Bavarian Nordic. G. Fiore: A. Employment (full or part-time); Significant; Bavarian Nordic. S. Wennier: A. Employment (full or part-time); Significant; Bavarian Nordic. P. Chaplin: A. Employment (full or part-time); Significant; Bavarian Nordic. M. Suter: A. Employment (full or part-time); Significant; Bavarian Nordic. H. Hochrein: A. Employment (full or part-time); Significant; Bavarian Nordic. H. Lauterbach: A. Employment (full or part-time); Significant; Bavarian Nordic.